Pengaruh Daya Tarik Wisata, Fasilitas dan Aksesibilitas terhadap Keputusan Berkunjung Wisatawan di Cambai Hill Alahan Panjang - Henryanto Abaharis; Fatiyah Izzati (Lembaga Yasin AlSys, 2026)
Studies on tourists’ visiting decisions have been widely conducted, but research that specifically examines the influence of tourist attraction, facilities, and accessibility at the Cambai Hill Alahan Panjang tourist attraction remains limited. This study aims to analyze the influence of tourist attraction, facilities, and accessibility on tourists’ visiting decisions. This study used a quantitative approach with a survey design. The research respondents consisted of 100 tourists who visited Cambai Hill Alahan Panjang and were determined using the Yamane formula. Data were collected through a questionnaire, then analyzed through validity testing, reliability testing, multiple linear regression analysis, and hypothesis testing with the assistance of the SPSS program. The results showed that tourist attraction had a positive and significant effect on tourists’ visiting decisions. Facilities also had a positive and significant effect on tourists’ visiting decisions. Meanwhile, accessibility had no significant effect on visiting decisions. These findings expand understanding of the factors that influence tourist behavior at natural tourism destinations. The implications of this study emphasize the importance for tourism managers to improve the quality of tourist attractions and facilities as a strategy to encourage tourists’ visiting decisions.